A Correlation Study Between Ankle Brachial Pressure Index and the Severity of Coronary Artery Disease - Benyakorn T. (2014)
Previous studies have shown that there was a correlation between low ankle brachial pressure index (ABPI) and the presence of the coronary artery disease (CAD). However, few studies have investigated the correlation between ABPI and the severity of CAD by using a scoring system. The authors aimed to investigate this correlation by using ABPI and CAD diagnosed by coronary angiography (CAG). A total of 213 consecutive patients awaiting CAG in Maharaj Nakorn Chiang Mai Hospital from July 2009 to November 2009 were enrolled in this study. The ABPI was measured before CAG. The severity of CAD was graded on CAG by using SYNTAX scores. The authors found a significantly negative correlation between ABPI and SYNTAX scores (correlation coefficient = -.172, P =.01). The authors concluded that ABPI appeared to correlate negatively with the severity of CAD in the Thai population. © The Author(s) 2012.